The Legal Protection for Patent Holders in Divided Infringement in Indonesia - Girindra, Ida Ayu Vipra; Kusumadara, Afifah; Widyanti, Yenny Eta (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2024)
This research aims to analyze the elements of patent infringement in divided infringement cases and the legal protection for patent holders in Indonesia. The research employs a normative juridical research method, selected due to the legal vacuum. The approaches used include the Legislative Approach, Comparative Approach, and Case Approach, which collectively establish guidelines regarding the key issues addressed in this study. The research findings reveal that current Indonesian patent law, as outlined in Law No. 13 of 2016, does not regulate the elements present in divided infringement, leading to legal gaps in protecting patent holders. The absence of provisions for indirect infringement leaves patent holders vulnerable and limits their ability to seek compensation from those who contribute to violations in divided infringement. To address these issues, the article recommends that Indonesia adapt regulations encompassing indirect infringement and enhance the legal framework protecting the exclusive rights of patent holders. This adaptation would not only promote innovation but also provide clearer avenues for legal recourse against parties contributing to patent infringement, thereby reinforcing the enforcement of intellectual property rights in Indonesia.